A Reterospective Study to Asses the Prevalence of Type 2 Diabetes Mellitus among Patient with Chronic Liver Disease at a Selected Hospital in Kancheepuram District, Tamil Nadu (Medico Legal Update, 2020)
A Retrospective study was conducted to assess the prevalence of type 2DM among chronic liver disease ina selected hospital at Kelambakkam, Tamil Nadu. The objectives were to assess the prevalence of type 2DMamong patient with chronic liver disease by collecting the data from the medical records of the patients andto find the association between type 2 diabetes mellitus with the selected demographic variables amongpatient with chronic liver disease. The literature review was done and organised under various aspects onstudies related to prevalence of type 2DM among patients with CLD. The research approach used for thestudy was quantitative approach and the design was non- experimental retrospective design, 50 sampleswere participated in the study by using convenient sampling technique. Demographic variables are assessedby using the statistical measurement and prevalence of type 2DM among patient with chronic liver disease.The level significance selected was p